Produksi Bare Life Melalui Stigma Sosial dan Regulasi Kekuasaan Terhadap Pemabuk di Indonesia - Muhammad Fadlan H. Daud (Universitas Islam Darul Ulum Lamongan, 2025)
This study aims to examine the position, status, and social experiences of alcoholics in Indonesia through the perspective of Giorgio Agamben's political philosophy, particularly the concepts of bare life and state of exception. In religious countries such as Indonesia, alcohol consumption is considered a violation of religious, social, and legal norms. As a result, alcoholics experience stigmatization, discrimination, and strict regulations that place them outside the scope of social and political protection. Using qualitative methods and literature studies, this research analyzes secondary data from various academic literature such as scientific articles, books, and related documents obtained through Google Scholar, Semantic Scholar, and Open Knowledge. The results show that alcoholics are not only subject to moral and legal sanctions, but are also reduced to bare life, that is, a life that is only recognized biologically but not protected as a complete political-legal subject. On the other hand, drunkards themselves interpret alcohol consumption as a form of emotional escape, a symbol of togetherness, or even resistance to social pressure. This study concludes that the mechanisms of stigma and regulation work together to alienate drunkards from legitimate public spaces, thus recommending a more humanistic, educational, and rehabilitation-based approach rather than criminalization.